Estimation and Interpretation of Financial Leverage - Mackevičius, Jonas; Poškaitė, Dalia (Ekonomika, 2003)
In competitive market conditions business financing is an up-to date issue because of the limited business financing resources. There for it is important not only to find business financing resources, but also to choose rational structure.Authors disagree at this particulars issue. but this article emphasizes the overall experience proclaiming that the ratio of the financial leverage experience proclaiming that the ratio of the financial leverage, based on liability and owner’s equity, is the most commonly used. The methodic of these calculations depend on the specific features of the country’s accounting system, in particular it’s financial statements.The main appropriate way to calculate the financial leverage in Lithuania is using long term liability and owner’s equity ratio. Analyzing company’s financial risk and stability, other modifications of this ratio and additional ratios as operating and common leverage ratios, indiferent point and others can be used.The advantage of the financial leverage ratio is the possibility not only to evaluate the financial balance, but also to choose the most rational fixed capital structure.Calculations indicate, that the best financial leverage coefficient is 0.5, showing the financing structure consisting of 33.3% long term liability and 66.7% of owner’s equity, as only them the financial balance is achieved. Deviation to one or another side can be accepted in achieving particles goals and evaluating the factors of the internal and external environment, effecting the financial status of the company.